A Voice from the Margins: An Appraisal of Ubaid-Allah Sindhi’s Mahabharat Sarvrajia Party and its Constitution - Tanvir Anjum (Journal of Political Studies, 2013)
Ubaid-Allah Sindhi is among those very few political thinkers and activists of the twentieth-century India who were initially associated with the traditional theological seminaries but their political vision was marked by liberalism and openmindedness. He established a non-communal political party— Mahabharat Sarvrajia Party in 1924 in order to translate his political ideals into practice. The Party Constitution envisaged the idea of a unique form of confederal form of government for the country. It also presented an outline of a socio-economic order which was derived from a reconciliation of Socialist ideals with the Quran and Shah Wali-Allahi thought. However, he is among one of the least understood and often misinterpreted Muslim thinkers of India. Thus, there is a need to appreciate and reevaluate the political modernism in his thought and vision.